MANAJEMEN PERILAKU PROKRASTINASI AKADEMIK MAHASISWA SELAMA PEMBELAJARAN DARING - IMAM TURMUDI; SURYADI SURYADI (Universitas Islam Negeri Mataram, 2021)
Online learning for students has an impact on the tendency to delay or not do an assignment. This is an indication of procrastination behavior. Procrastination behavior in general is a behavior to do a task when Injury time or task collection limit. This will make procrastinators feel panicked. This feeling of panic can cause students to make bad decisions, namely to commit academic dishonesty. This study aims to describe the characteristics of students in doing academic procrastination during online learning. The research method uses qualitative research, data collection techniques using online google forms. The results of this study indicate that students during online learning do a lot of academic procrastination among: first, delaying assignments in the hope of getting more time to complete academic assignments 1.3%, second, assignments given by lecturers are too difficult 2.7%, third, difficult to find material 14.7%, fourth, difficult to get a wifi signal 20%, fifth, boring lecturer teaching methods 26.7%, sixth, poor time management 10.7%, seventh, attaching importance to other things 5.3%, eighth, helping parents at home 18.7%.